Predicting pre-service teachers' success in Nigeria Certificate Education(NCE) mathematics (2008)
The success of one hundred and eight-seven final year pre-service teachers in NCE mathematics was predicted with five variables namely, age, SSCE/NECO/GCE mathematics grade, further mathematics grade, hours of mathematics study and average number of books consulted in the study of mathematics. A close ended questionnaire was used to collect data from the pre-service teachers and stepwise discriminant analysis was run. Results revealed that group differences were significant for all the variables except number of books consulted in the study of mathematics while further mathematics grade was found to be most associated with the function. These results suggested that the pre-service teachers who had a good SSCE/NECO/GCE grade in further mathematics are likely to be successful in NCE mathematics. It was therefore recommended that candidates that intend to study mathematics at the tetiary level in general and the Nigeria certificate of Education (NCE) level in particular must have attempted and passed further mathematics at the Senior Secondary Certificate level